The role of evaluation in strengthening agricultural R&D in sub-saharan Africa: information, instruments, and actors - Oruko, Leonard; Elliott, Howard (International Food Policy Research Institute, 2011)
This paper links the evolution of research monitoring and evaluation (M&E) tools to major questions being asked and to demands for research reform at the global, regional, subregional, and national levels. First, in order to inform decisionmaking, research must continuously push the frontiers, conceptually and computationally, while providing practical considerations to policymakers and their advisers. Second, the demand for new concepts and tools is continuously evolving as problems are redefined: each successful study enhances the demand for better data and better tools. Finally, monitoring paces the reform process in three critical ways: (1) it corrects pathways to new objectives as needed; (2) it measures the efficiency and effectiveness of implementation; and (3) it identifies organizational, institutional, and systemic constraints to achievement of objectives. This paper interprets several key reforms at national and international levels; relates them to the M&E tools used; and draws some conclusions for the future development of data, information, and analytical approaches in Sub-Saharan Africa.